Processing and reporting monitoring and evaluation data - Mercado, Cesar Matamorosa 1938- (Development Consultants for Asia Africa Pacific, 2004)
Purpose: A compilation of four articles of Cesar M. Mercado PH.D which illustrates the whole process in processing and reporting."